MicroRNAs Circulate in the Hemolymph of Drosophila and Accumulate Relative to Tissue microRNAs in an Age-Dependent Manner - Dhahbi, Joseph M. (Genomics Insights, 2016)
In mammals, extracellular miRNAs circulate in biofluids as stable entities that are secreted by normal and diseased tissues, and can enter cells and regulate gene expression. Drosophila melanogaster is a proven system for the study of human diseases. They have an open circulatory system in which hemolymph (HL) circulates in direct contact with all internal organs, in a manner analogous to vertebrate blood plasma. Here, we show using deep sequencing that Drosophila HL contains RNase-resistant circulating miRNAs (HL-miRNAs). Limited subsets of body tissue miRNAs (BT-miRNAs) accumulated in HL, suggesting that they may be specifically released from cells or particularly stable in HL. Alternatively, they might arise from specific cells, such as hemocytes, that are in intimate contact with HL. Young and old flies accumulated unique populations of HL-miRNAs, suggesting that their accumulation is responsive to the physiological status of the fly. These HL-miRNAs in flies may function similar to the miRNAs circulating in mammalian biofluids. The discovery of these HL-miRNAs will provide a new venue for health and disease-related research in Drosophila.